Reducing GHG emissions through efficient tire consumption in open pit mines. (10th May 2020) - Rodovalho, Edmo; Quaglio, Osvail; Felsch Junior, Walter Schmidt; Pascual, Rodrigo; de Tomi, Giorgio; Soares Tenório, Jorge Alberto
Abstract: The waste management practices currently applied by the mining industry have been widely questioned regarding safety and efficiency. It is not by chance that the mining industry is considered one of the sectors with less integration in circular value chains. The present work is aimed at identifying the specific blend of lithologies applicable to haul road wearing coarse materials with the objective of increasing tire efficiency and reducing of waste tire rubber generation. The methodology includes the physical characterization of waste lithologies as the first stage to evaluate applications for environmental and economic performance improvement. Simulation models generated through multiple linear regression can identify the impact of waste rock application on tire performance. In addition, methods and practical applications that consider the use of wastes as a construction material for haul roads to reduce tire wearing is a novelty. Regarding a 5-year mine scheduling context, the combination of the simulation model applied to tire wear management and the new haul road maintenance method reached a reduction of 30.2 kt per year of waste tire rubber in an open pit mine. Considering the burning of these tires in cement kilns, this result also implies a reduction of 86.1 t of CO2 emissions per year. These practices are aligned with sustainable mining concepts and can contribute to the maintenance of social licenses of the mining industry. Highlights: Waste management practices applied to mining and aligned to circular value chains. An innovative method of waste rock types selection applied to haul road maintenance. Additional production of over 4.3 million t, attributed to greater tire efficiency. The described application can avoid 86.1 t of CO2 emissions per year.